Inhaled pirfenidone solution (AP01) for IPF: a randomised, open-label, dose-response trial - West, Alex; Chaudhuri, Nazia; Barczyk, Adam; Wilsher, Margaret L; Hopkins, Peter; Glaspole, Ian; Corte, Tamera Jo; Šterclová, Martina; Veale, Antony; Jassem, Ewa; Wijsenbeek, Marlies S; Grainge, Christopher; et al. (Thorax, 2023)
INTRODUCTION: Oral pirfenidone reduces lung function decline and mortality in patients with idiopathic pulmonary fibrosis (IPF). Systemic exposure can have significant side effects, including nausea, rash, photosensitivity, weight loss and fatigue. Reduced doses may be suboptimal in slowing disease progression. METHODS: This phase 1b, randomised, open-label, dose-response trial at 25 sites in six countries (Australian New Zealand Clinical Trials Registry (ANZCTR) registration number ACTRN12618001838202) assessed safety, tolerability and efficacy of inhaled pirfenidone (AP01) in IPF. Patients diagnosed within 5 years, with forced vital capacity (FVC) 40%-90% predicted, and intolerant, unwilling or ineligible for oral pirfenidone or nintedanib were randomly assigned 1:1 to nebulised AP01 50 mg once per day or 100 mg two times per day for up to 72 weeks. RESULTS: We present results for week 24, the primary endpoint and week 48 for comparability with published trials of antifibrotics. Week 72 data will be reported as a separate analysis pooled with the ongoing open-label extension study. Ninety-one patients (50 mg once per day: n=46, 100 mg two times per day: n=45) were enrolled from May 2019 to April 2020. The most common treatment-related adverse events (frequency, % of patients) were all mild or moderate and included cough (14, 15.4%), rash (11, 12.1%), nausea (8, 8.8%), throat irritation (5, 5.5%), fatigue (4, 4.4%) and taste disorder, dizziness and dyspnoea (three each, 3.3%). Changes in FVC % predicted over 24 and 48 weeks, respectively, were -2.5 (95% CI -5.3 to 0.4, -88 mL) and -4.9 (-7.5 to -2.3,-188 mL) in the 50 mg once per day and 0.6 (-2.2 to 3.4, 10 mL) and -0.4 (-3.2 to 2.3, -34 mL) in the 100 mg two times per day group. DISCUSSION: Side effects commonly associated with oral pirfenidone in other clinical trials were less frequent with AP01. Mean FVC % predicted remained stable in the 100 mg two times per day group. Further study of AP01 is warranted. TRIAL REGISTRATION NUMBER: ACTRN12618001838202 Australian New Zealand Clinical Trials Registry.
Keywords: výsledek terapie; Austrálie; Male; pyridony; idiopatická plicní fibróza; Idiopathic Pulmonary Fibrosis; Aged; mužské pohlaví; senioři; Pyridones; Anti-Inflammatory Agents, Non-Steroidal; Treatment Outcome; antiflogistika nesteroidní; vitální kapacita; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; Australia; Female; lidé středního věku; Vital Capacity; Middle Aged